1983
DOI: 10.1161/01.res.53.1.42
|View full text |Cite
|
Sign up to set email alerts
|

Role of adenosine in the maintenance of coronary vasodilation distal to a severe coronary artery stenosis. Observations in conscious domestic swine.

Abstract: SUMMARY. The purpose of this study was to test the hypothesis that adenosine is required to maintain arteriolar vasodilation distal to a severe coronary stenosis. Eight closed-chest conscious pigs were prepared by placing a 7.5-mm long stenosis (82% lumenal diameter reduction) in the proximal left anterior descending coronary artery. Regional myocardial blood flow (microsphere technique) was measured at control 1, after 10 minutes of intracoronary infusion of adenosine deaminase (7-10 U/kg per min) distal to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…Previous studies have demonstrated that endogenous adenosine is not obligatory for maintaining coronary blood flow during normal arterial inflow. Thus, studies in anesthetized open-chest dogs (15)(16)(17)(18)(19) and awake dogs (1,20) failed to demonstrate an effect of intracoronary adenosine deaminase (15)(16)(17), or adenosine receptor blockade with intravenous aminophylline (18, 19) or 8-phenyltheophylline (1, 20), on (21) examined the effect of exercise on myocardial adenosine production. They found that treadmill exercise in dogs resulted in a fivefold increase in myocardial adenosine content, with a doubling of the coronary arterio-venous adenosine content difference.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that endogenous adenosine is not obligatory for maintaining coronary blood flow during normal arterial inflow. Thus, studies in anesthetized open-chest dogs (15)(16)(17)(18)(19) and awake dogs (1,20) failed to demonstrate an effect of intracoronary adenosine deaminase (15)(16)(17), or adenosine receptor blockade with intravenous aminophylline (18, 19) or 8-phenyltheophylline (1, 20), on (21) examined the effect of exercise on myocardial adenosine production. They found that treadmill exercise in dogs resulted in a fivefold increase in myocardial adenosine content, with a doubling of the coronary arterio-venous adenosine content difference.…”
Section: Discussionmentioning
confidence: 99%
“…Although other mediators may substitute for low pH or elevated Pco2, results of earlier studies conducted in our laboratory indicate that sustained elevation of interstitial fluid adenosine concentration19 or increased prostacyclin production32 also are not essential for long-term maintenance of reduced arteriolar tone distal to a severe coronary arterial stenosis. Thus, the results of the present investigation are best understood in the context of a series of experiments, [16][17][18][19]31,32 which indicate that known mediators of acute changes in coronary arteriolar tone may not have an important role (either alone or in combination) in the long-term maintenance of reduced arteriolar tone distal to a severe coronary arterial stenosis. The mechanism(s) involved in maintenance of reduced coronary arteriolar tone in this setting is unknown but could involve alterations in one or more proteins responsible for regulation of vascular smooth muscle contraction and relaxation.…”
Section: Discussionmentioning
confidence: 84%
“…69 - 70 The absence of reduction in myocardial blood flow by adenosine deaminase administered distal to a coronary stenosis also indicates that adenosine contributes only modestly to maintenance of arteriolar vasodilation in hypoperfused hearts. 70 Failure to resolve this controversy may be due to the fact that adenosine deaminase has not been clearly demonstrated to destroy all of the adenosine in the interstitial space. 71 In addition, factors other than adenosine may be involved in flow changes during ischemia and hypoxia.…”
Section: Adenosine For Coronary Vasodilation In Ischemic Heartsmentioning
confidence: 99%